Facial morphology and growth following surgery for congenital midline cervical cleft patients. Issue 4 (April 2018) - Fan, Y.; Matthews, H.; Kilpatrick, N.; Claes, P.; Clement, J.; Penington, A.
Abstract: Congenital midline cervical cleft (CMCC) is a rare condition that consists of a cutaneous midline neck lesion with a sinus extending inferiorly towards the sternum. A fibrous band that extends superiorly to the mandible is a consistent feature of the condition. Restriction of growth of the mandible, possibly due to incomplete removal of the band, is the most significant long-term problem. It remains unclear whether early removal of the fibrous band might allow catch-up growth of the mandible. This study utilized non-invasive three-dimensional photographs to objectively evaluate the facial growth of six CMCC patients. The growth of these CMCC patients was compared to the average growth of age- and sex-matched controls from a database of three-dimensional facial photographs of clinically normal subjects. After surgical removal of the fibrous cord, CMCC patients experience growth in the chin at the same rate as in the normal population; no evidence was found for catch-up growth. As a result, individuals with CMCC are likely to require further surgical intervention to correct the residual retrognathia on completion of facial growth. Early excision of the lesion including aggressive resection of the fibrous band is still recommended, as this should optimize the early growth of the mandible in infancy.